Soil invertebrates of deciduous forests after clear cutting ... - Alla Kolesnikova (Mendeley, 2021)
The list of taxa of large soil invertebrates and microarthropods (with their abundance) collected in the deciduous forests after clear cutting is presented in Table. The research was carried out in two plots which located in the middle taiga zone of Komi Republic (near Syktyvkar city), european part of Russia. Plot 1 is a 25-year-old birch-spruce forest of a forb type. Plot 2 is a 54-year-old aspen-birch forest of a blueberry-forb type. Despite similar soil conditions and the original type of spruce forest, the plots differ the stock of forest litter. The litter capacity is 46.1 ± 19.3 t / ha in the birch-spruce forest. This parameter is only 40.0 ± 11.6 t / ha in the aspen-birch forest. The soil sampling method was chosen for collecting of invertebrates. As a result, 16 taxa of soil invertebrates were revealed In the birch-spruce forest. Oribatida and Collembola were abundant groups among mesofauna, Diptera was a dominant group among macrofauna. The same taxa, with the exception of Dytiscidae and ...